Rural Electrification: Prospects, Challenges and Role of Community for Bulk Buying Method in Rural Municipality of Lalitpur District - Parajuli, Pradip (Patan Prospective Journal, 2022)
Rural electrification is the process of bringing electrical power to rural and remote areas. Bulk buying method in rural electrification is when a licensed organization (cooperative in this case) buys electricity from NEA in bulk in cheaper price and distributes it to rural areas in normal prices. The profit generated will be used in the maintenance and expansion of the electric grid lines. The profit is also used in different awareness programs and uses of electricity. The Rural electrification via bulk buying method is a new type of rural electrification process. Despite this being used in some parts of Nepal from 2061 BS, it is not a wide spread process and people don’t know about it. The objective of this study is to find out about the benefit of this method over other electrification methods like solar, small hydropower plants. The different difficulties and hinder and faced by the rural population as well as the organizations trying to implement this process. The role of the community in the implementation and sustainability of this process and how it will impact their life. This methodology focuses on answering questions relating to “what” than the “why” of rural electrification. Descriptive as well as analytical methods are being used. Observation of the place and who the bulk buying method is being used and survey of the people was done for Descriptive method. Analysis method refers to the process of analyzing survey results from universe of the study. Rural areas are very isolated and the communities there have very different lifestyles than those of us living in urban areas where electricity is given. Rural electrification with the use improves individual’s quality of life, enables community services such as health and education (consumption use) and enables business entities to carry out professional activities (productive use) for rural populations. All of these benefits are possible without creating unintended negative consequences for local ecosystems and the global climate. Some people don’t believe that this process is good for these communities, but the advantages clearly show that electrification will benefit them and improve their quality of life.